2011
DOI: 10.1016/j.joi.2011.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Mapping excellence in the geography of science: An approach based on Scopus data

Abstract: As research becomes an ever more globalized activity, there is growing interest in national and international comparisons of standards and quality in different countries and regions. A sign for this trend is the increasing interest in rankings of universities according to their research performance, both inside but also outside the scientific environment. New methods presented in this paper, enable us to map centers of excellence around the world using programs that are freely available. Based on Scopus data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 24 publications
0
53
0
3
Order By: Relevance
“…Además, las visualizaciones reflejan las áreas o disciplinas del conocimiento donde han sido publicados los nuevos conocimientos producidos en el campo de la nanomedicina en México. En su conjunto, estos resultados son conocidos como mapas de la ciencia 14,15 , y visualizarlos desde la perspectiva de las disciplinas presentes en el desarrollo de nuevos conocimientos nos puede revelar las relaciones entre las diversas disciplinas en la producción y la acumulación de nuevos conocimientos. Además, este tipo de visualizaciones pueden aportarnos indicios de las dinámicas en los procesos de convergencia de conocimientos en campos emergentes.…”
Section: Metodosunclassified
See 1 more Smart Citation
“…Además, las visualizaciones reflejan las áreas o disciplinas del conocimiento donde han sido publicados los nuevos conocimientos producidos en el campo de la nanomedicina en México. En su conjunto, estos resultados son conocidos como mapas de la ciencia 14,15 , y visualizarlos desde la perspectiva de las disciplinas presentes en el desarrollo de nuevos conocimientos nos puede revelar las relaciones entre las diversas disciplinas en la producción y la acumulación de nuevos conocimientos. Además, este tipo de visualizaciones pueden aportarnos indicios de las dinámicas en los procesos de convergencia de conocimientos en campos emergentes.…”
Section: Metodosunclassified
“…En este apartado nos interesa revisar otra perspectiva de la visualización basada en las disciplinas del conocimiento, así como sus relaciones en la producción de nuevos conocimientos. Los resultados de estas técnicas de visualización se conocen como mapas de la ciencia 14,15 , y los datos de entrada son las categorías donde son indizadas las revistas científicas en las cuales han sido publicados los artículos científicos.…”
Section: áReas Del Conocimientounclassified
“…In addition to providing public goods, NRIs should also be actively involved in various social and academic activities to expand their academic and social influences. At present, some researches on the scientific map have shown that the prestigious research institutions in the international academic community are often located at the centres of the academic exchange network, which means that the academic social network will have a positive external effect on scientific research (Bornmann et al, 2011). In addition, NRIs also need to provide some public services for the society, such as the activities to popularise scientific knowledge and provide advisory reports.…”
Section: Graduate Training Processmentioning
confidence: 99%
“…In an article published in Nature News, van Noorden (2010) discusses which urban regions produce the best research in the world, and whether their success can be replicated. Bornmann, Leydesdorff, Walch-Solimena, & Ettl (2011) and Bornmann & Waltman (2011) classify cities and urban regions as "centers of excellence in scientific research", based on the total number of excellent papers (top 1% most highly cited papers). , and Bornmann & Leydesdorff (2012) examine whether there is a relationship between the total scientific output of cities and the number of highly cited papers published in those cities.…”
Section: Introductionmentioning
confidence: 99%